The Transcriptome and Metabolome Reveal Stress Responses in Sulfur-Fumigated Cucumber (Cucumis sativus L.) - Liu, Juan; Gao, Yang; Gong, Feifei; Hou, Feifan; Zhang, Zhipeng; Cheng, Xiaojing; Du, Wei; Zhang, Lingling; Wang, Jinyao; Xu, Jin; Xing, Guoming; Kang, Xiuping; et al. (Frontiers in Plant Science, 2021)
Sulfur fumigation is a commonly used sterilization method in horticultural facilities against fungal diseases. Sulfur fumigation damaged cucumber leaves, although the response mechanism is unclear. This study analyzed the growth, transcriptome, and metabolomic profiles of young and mature leaves, ovaries, and commercial cucumber fruits to decipher the mechanism of cucumber stress response under sulfur fumigation. Sulfur fumigation significantly changed the photosynthetic efficiency and reactive oxygen species in leaves, but not fruit development, fruit mass, and peel color. Transcriptome analysis indicated that sulfur fumigation strongly regulated stress defense genes. The weighted gene co-expression network analysis revealed that sulfur fumigation regulated ASPG1, AMC1 defense genes and LECRK3, PERK1 protein kinase. The ABA-mediated model of regulation under sulfur fumigation was constructed. Metabolome analysis showed that sulfur fumigation significantly upregulated or downregulated the contents of amino acids, organic acids, sugars， glycosides and lipids (VIP > 1, P-value < 0.05). The opposite Pearson correlations of these differential metabolites implied that cucumber had different metabolic patterns in short-term and long-term sulfur fumigation. Besides, the elevated levels of proline and triglyceride indicated that stress responsive mechanism existed in sulfur-fumigated cucumber. Moreover, comprehensive analysis indicated that sulfur fumigation elevated secondary sulfur-containing metabolites but decreased sulfate absorption and transportation in cucumber. Overall, our results provided comprehensive assessment of sulfur fumigation on cucumber, which laid theoretical foundation for sulfur fumigation in protected cultivation.